Endogeneous tradability and macroeconomic implications - Paul Bergin; Reuven Glick (University of California, Department of Economics, 2005)
This paper advocates a new way of thinking about goods trade in an open economy macro model. It develops a simple method for analyzing trade costs that are heterogeneous among a continuum of goods, and it explores how these costs determine the endogenous decision by a seller of whether to trade a good internationally. This way of thinking offers new insights into international market integration and the behavior of international relative prices. As one example, it provides a natural explanation for a prominent and controversial puzzle in international macroeconomics regarding the surprisingly low degree of volatility in the relative price of nontraded goods. Because tradedness is an endogenous decision, the good on the margin forms a link holding together the prices of traded and nontraded goods. The paper goes on to find that endogenizing trade has implications for other basic macroeconomic issues.
Keywords: F40; 330